2019
DOI: 10.1186/s12943-019-0955-9
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear lncRNA HOXD-AS1 suppresses colorectal carcinoma growth and metastasis via inhibiting HOXD3-induced integrin β3 transcriptional activating and MAPK/AKT signalling

Abstract: Background Long noncoding RNAs (lncRNAs) have been indicated to play critical roles in cancer development and progression. LncRNA HOXD cluster antisense RNA1 (HOXD-AS1) has recently been found to be dysregulated in several cancers. However, the expression levels, cellular localization, precise function and mechanism of HOXD-AS1 in colorectal carcinoma (CRC) are largely unknown. Methods Real-time PCR and in situ hybridization were used to detect the expression of HOXD-AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 48 publications
2
77
0
Order By: Relevance
“…Indeed, many lncRNAs have been identified to function in these pathways, such as TSLNC8, suppresses metastasis by inactivating the IL‐6/STAT3 signaling pathway 44 . HOXD‐AS1 inhibits colorectal cell growth and metastasis through inactivation of the MAPK/AKT signaling pathway 8 . Furthermore, we proved that Linc00839 overexpression could activate the phosphorylation of Akt, STAT3, and P38, but the expression level of p‐ERK1/2 was inactivated.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Indeed, many lncRNAs have been identified to function in these pathways, such as TSLNC8, suppresses metastasis by inactivating the IL‐6/STAT3 signaling pathway 44 . HOXD‐AS1 inhibits colorectal cell growth and metastasis through inactivation of the MAPK/AKT signaling pathway 8 . Furthermore, we proved that Linc00839 overexpression could activate the phosphorylation of Akt, STAT3, and P38, but the expression level of p‐ERK1/2 was inactivated.…”
Section: Discussionmentioning
confidence: 69%
“…Long noncoding RNAs (lncRNAs) have been identified as crucial components in BC development, 3 suggesting their potential abilities as diagnostic and therapeutic biomarkers 4 . Studies have shown that dysregulation of lncRNAs contributes to tumorigenesis, 5,6 metastasis, 7,8 and chemoresistance, 9 by modulating cell proliferation, 10 and apoptosis 11 through different signaling pathways. Different types of lncRNAs localize to the cytoplasm or nucleus, participating in transcriptional and posttranscriptional gene expression 12 .…”
Section: Introductionmentioning
confidence: 99%
“…increasing evidence suggests that long non-coding rnas (lncrnas) are involved in the occurrence and progression of ccrcc (2)(3)(4)6). lncrnas, defined as transcribed rna molecules >200 nt in length (9)(10)(11)(12), are an important class of non-coding rnas involved in several biological functions (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…antisense lncrnas (aS lncrnas), a subclass of lncrnas, are transcribed from complex genetic loci on the opposite strands of sense protein-coding genes (13)(14)(15)(18)(19)(20). aS lncrnas may overlap exons and/or introns of their associated sense protein-coding transcripts to regulate epigenetic silencing, transcription and mrna stability by forming sense-antisense pairs (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are de ned as a novel class of RNA molecules of length more than 200 nucleotides with narrow protein coding functions [4,5]. Recently, a growing body of research has revealed that lncRNAs have been implicated in the tumorigenicity of multiple cancers, including CRC [6][7][8]. Dysregulated lncRNAs have been demonstrated to work as oncogenes or tumor suppressors through affecting a wide spectrum of biological activities, such as cell growth, invasion, metastasis and autophagy [9,10].…”
Section: Introductionmentioning
confidence: 99%